Diagnostic Accuracy of CHROMagar MRSA for Detection of Methicillin-Resistant Staphylococcus Aureus (MRSA) from Screening Swab Specimens - Ahmed, Farooq; Hussain, Wajid; Mirza, Irfan Ali; Ali, Saad; Khurshid, Umar; Sarwar, Mariam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of CHROMagar MRSA for detecting MRSA from screening swab specimens keeping the Cefoxitin disk diffusion test as the reference method.Study Design: A cross-sectional validation study.Place and duration of study: Department of Microbiology, Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Mar to Aug 2019.Methodology: A total of 243 screening swab specimens, e.g., axillary, nasal and web swabs, each of hospitalized patients and healthcare workers (HCW) submitted for MRSA screening were included in the study and were processed simultaneously on blood agar, MacConkey agar and CHROMagar MRSA. The agar plates were incubated at 35°C ± 2°C for 18-24 hours in ambient air. The cefoxitin disk diffusion test followed the isolation and identification of MRSA according to the latest Clinical and Laboratory Standards Institute (CLSI) guidelines. In CHROMagar MRSA screening, after incubation, plates were examined for the presence of mauve colonies (MRSA detected), and the results were obtained and validated against the reference method of Cefoxitin disk diffusion.Results: Overall, the diagnostic accuracy of CHROMagar MRSA for detecting MRSA was 97.53%. Diagnostic accuracy of CHROMagar MRSA was 95.1%, 97.5% and 100% in axillary, nasal and web specimens, respectively. The rate of MRSA detection was maximum in axillary swabs, i.e., 40.7%, followed by 29.6% and 9.8% in nasal and web swabs, respectively.Conclusion: CHROMagar MRSA is found to be accurate for the detection of MRSA. It is reliable, easy to perform, less timeconsuming, and cost-effective. It is an affordable alternative to the conventional..............